Modeling Ground Access Traffic Based On Air Passenger Data In Juanda International Airport - Wiryanta Wiryanta; Ervina Ahyudanari (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Institut Teknologi Sepuluh Nopember, 2018)
Airport attracts large scale of demand to travel in. Most air travelers use private cars or taxi to reach and leave the airport. This number leads to congestion and reducing the quality of air in and around airport. The effect of increasing number of air traveler to the quality of ground access demands the airport to re-evaluate the design of the available access mode. To evaluate the available design of access mode, this study requires data of air travelers as well as the airplane schedules in Juanda International Airport Surabaya. The data incorporate the economic growth results in prediction of future demand that will occupy the road access to airport. This research attempts to build a model to generate potential passengers in inducing traffic congestion. This model suggests the period of airport operational to develop alternative access modes to reduce the congestion level. The model shows that in 2020, every air traveler generates 3.6 vehicle trips of ground access traffic.